Kinetic study of the partial hydrogenation of 1-heptyne on tungsten oxide supported on alumina - Maccarrone, María Juliana (2012)
BACKGROUND: Partial hydrogenation of alkynes have industrial and academic relevance on a large scale; industries such as petrochemical, pharmacology and agrochemical use these compounds as raw material. Typical commercial catalysts contains palladium. Finding an economic, active and selective catalyst for the production of alkenes via partial hydrogenation of alkynes is thus an important challenge. On the other hand, the literature on kinetic studies of partial hydrogenation of heavy alkynes is scarce. So the main objectives of this work were to prepare a cheaper catalyst based on low W loading, and study the kinetic of the partial hydrogenation of 1-heptyne. A pseudo-homogeneous and six heterogeneous kinetic models were analyzed. The catalyst was characterized by ICP, XPS, DRX, TPR and hydrogen chemisorption techniques. RESULTS: The characterization results indicate that only WO x species are present on the alumina surface. The WO x/Al 2O 3 catalyst was active and selective for producing 1-heptene even at low reaction temperatures, the partial hydrogenation of 1-heptyne proceeds via two irreversible reactions in parallel. CONCLUSION: The best fit of the experimental data was achieved with a heterogeneous Langmuir-Hinshelwood-Hougen-Watson model in which the rate controlling step is the dissociative adsorption of hydrogen. The activation energy was estimated as E H2 = 34.8 kJ mol -1.